Comprehensive Approach to Accelerate Tuberculosis Case Finding among Women and Children Under Five in Rural Indonesia - Margareta Teli; Simon Sani Kleden; Irfan; Aemilianus Mau; Wanti; Pius Selasa; Maria Hilaria; Maria F. Vinsensia D.P. Kewa Niron; Yualeny Valensia; Oklan B.T. Liunokas; Marni Tangkelani; Matje M. Huru (Poltekita: Jurnal Pengabdian Masyarakat, 2025)
Tuberculosis (TB) continues to be a major worldwide health concern, with some regions in Indonesia facing challenges in achieving case detection objectives. This initiative sought to enhance tuberculosis case detection using mobile X-ray screening, the provision of preventative medication, and the identification of latent tuberculosis infections among household contacts and high-risk groups, especially stunting children. The results indicated that just 6.03% of participants had a history of tuberculosis contact, but 67.84% presented risk factors including malnutrition, exposure to smoking, previous tuberculosis diagnosis, and diabetes. Chest radiography revealed anomalies in 6.03% of individuals, requiring further diagnostic verification. Furthermore, stunting was widespread, with 48% categorized as moderately stunted and 27% as severely stunted. Post-intervention evaluations indicated an enhanced mother's understanding of tuberculosis. Initiatives to enhance tuberculosis case finding among women and children under five in rural regions must be expanded and strengthened to decrease transmission, enhance detection rates, bridge information gaps, mitigate stigma, and increase treatment coverage, ultimately leading to reduced tuberculosis transmission.